2022
DOI: 10.1186/s12885-022-09374-x
|View full text |Cite
|
Sign up to set email alerts
|

High ratio of pCXCR4/CXCR4 tumor infiltrating immune cells in primary high grade ovarian cancer is indicative for response to chemotherapy

Abstract: Background Ovarian cancer (OC) is the fifth most common malignant female cancer with a high mortality, mainly because of aggressive high-grade serous carcinomas (HGSOC), but also due to absence of specific early symptoms and effective detection strategies. The CXCL12-CXCR4 axis is considered to have a prognostic impact and to serve as potential therapeutic target. Therefore we investigated the role of pCXCR4 and CXCR4 expression of the tumor cells and of tumor infiltrating immune cells (TIC) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recent studies have demonstrated a strong link between IRGs and TIICs in several tumor types, notably osteosarcoma (16), breast cancer (42), and ovarian cancer (43). Thus, we looked deeper into the proportion of TIICs and how the risk score affected TIICs in PCa bone metastatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated a strong link between IRGs and TIICs in several tumor types, notably osteosarcoma (16), breast cancer (42), and ovarian cancer (43). Thus, we looked deeper into the proportion of TIICs and how the risk score affected TIICs in PCa bone metastatic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated a strong link between IRGs and TIICs in several tumor types, notably osteosarcoma [16], breast cancer [42], and ovarian cancer [43]. Thus, we looked deeper into the proportion of TIICs and how the risk score affected TIICs in PCa metastatic bone tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis of CXCL12, CD66b, OX40, IL-17, CXCR4, pCXCR4, FoxP3, MPO, and IL-22 protein expression from our previous studies was calculated using the Spearman’s correlation test (Posabella et al 2020 ; Ramser et al 2018 ; Walther et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%